Cycles, Continuous Progress, Automatic Promotion: contributions for the discuss - Regiane Helena Bertagna (Universidade Estadual Paulista Júlio de Mesquita Filho, 2009)
The present article aims to contribute for the discussion on the process of school organization starting from the concepts of cycles, continuous progress and automatic promotion. For that it was used the historical recover, the analysis of the official documents as well as of the literature that is pertinent to the subject, seeking the contextualization of the origin of those proposals and of the assessment conceptions that are underlying to them. The text tries to explain the subject of the cycles, of the continuous progress and automatic promotion/approval, analyzing how those ideas carry, potentially, the possibility of the professionals of the education possibility rediscuss the school organization and, implicitly, the marks of the education politics which propose them.